Self-Efficacy, Teacher Leadership and Teacher Professionalism in Secondary School - Anisa Rara Tyaningsih; Suryadi Suryadi; Desi Rahmawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The article was to determine the effect of self-efficacy on teacher professionalism, the effect of teacher leadership on teacher professionalism, and the effect of self-efficacy on teacher leadership. The research was conducted at 14 secondary school in West Jakarta, Indonesia by using survey method and testing the hypothesis with path analysis. Sample of this study consisted of 85 teachers selected by simple random sampling. The data collection technique was conducted by using an online questionnaire which was google form. The variable of self-efficacy includes learning strategies, class management, and student engagement. Then, the variable of teacher leadership includes four dimensions, namely collective leadership, leadership opportunity, leadership engagement, and supra-practitioner. Meanwhile, the teacher professionalism variable includes four domains, namely professional skills, autonomy in decision making, collaborative practice and commitment. The result shows that there was a positive direct effect of the self-efficacy variable on the teacher professionalism variable, there was a positive direct effect of the teacher leadership variable on the teacher professionalism variable and there was a positive direct effect of the self-efficacy variable on the teacher leadership variable. The result of the study was discussed by considering the relevant literature and implications were made. Keywords: Teacher Leadership, Teacher Professionalism, Secondary School